Efficiency of 3,4- dihydropyrimidin -2 (1H) Derivative Compounds in Inhibition Fungi Associated with Wheat Seeds - Ahmed Ihsan Flayyih Al-Jawhari (Journal of Global Pharma Technology, 2018)
This study conducted to synthesis and identification of 3,4 - dihydropyrimidin -2 (1H) derivative compounds , and also study the efficiency of these compounds in inhibition fungi associated with wheat seeds . The results showed that three compounds were synthesis and identificate by using Infrared spectroscopy (IR) , H-MMR and Mass spectroscopy . The result showed that three species of fungi were isolated from wheat seeds , these fungi were Rhizoctoniasolani , Trichodermalignorum and Aspergillusniger. The results obtained that compound ( 3a ) was more efficiency to inhibition all fungi isolated , and the statistical methods showed no significant between different concentrationsof compounds . Keywords: Dihydropyrimidin, Monastrol, Fungi, Fungicides, Wheat, Seeds.